Reinforcing the gear and cam drives of rescue equipment by autocatalytic hardcourt Ni-P covers - Reva Ольга; Kulakovskiy Борис; Makhan’ko Владимир; Bugaeva Е.; Lakhvich Вячеслав (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The optimum phase composition and microstructure of autocatalytic Ni-P coatings with high microhardness, wear and corrosion resistance were determined. The tests of the cam roller of vacuum shutter and parts of the winch serrate reel from rescue device, modified by Ni-P coatings, imitating their long-term work in the real conditions, were carried out. It was found, that hard wear-resistant Ni-P coatings increase the exploitation resource of the unit at most many 2 times.